Profil Kecerdasan Majemuk (Multiple Intelligences) dan Karakter Mahasiswa di Universitas Negeri Medan: Implikasi terhadap Pembelajaran Holistik - Alfi Mutiara Br Tumangger; Jultin Kasandra Buulolo; Nurul Amnah Siregar; Rizka Damayanti; Sofwatun Nabila; Yusri Delfinsta Sianturi (CV. Eracita Grup, 2026)
This study aims to describe the profile of multiple intelligences and character of students at the Faculty of Education, Universitas Negeri Medan, along with their demographic characteristics based on department, academic year, GPA, gender, and age. The research employed a quantitative approach using a descriptive research design. The subjects consisted of 25 students from the PGSD, PGPAUD, Guidance and Counseling, and Community Education programs. Data were collected through questionnaires distributed via Google Forms, including respondent identity data, the Multiple Intelligences Score (MIS) instrument, and a character instrument covering honesty, cooperation, discipline, care, independence, perseverance, resilience, initiative, responsibility, and communication ethics. Data were analyzed using descriptive statistics with the Jamovi application, including mean values, percentages, and frequency distributions. The results indicate that kinesthetic, interpersonal, intrapersonal, existential, musical, and naturalistic intelligences were relatively more developed among students, while logical-mathematical, verbal-linguistic, and visual-spatial intelligences were less dominant. Regarding character aspects, most students were categorized at a moderate level, with communication ethics emerging as the most prominent character trait. These findings highlight the importance of implementing holistic learning approaches that integrate multiple intelligences and character development in higher education.